Pancreatic pseudocyst: Spontaneous cysticjejunal fistula - Barquet, Alberto (Cirugía del Uruguay, 2021)
With reference to the subject "pancreatic cysts" dealt with in a former session, we present the case history of a pancreatic pseudocyst following grave acute pancreatitis. The evolution, medicosurgical treatment and constitution of a spontaneous cysticointestinal fistula in described. The author draws conclusions from this case.